A comparative analysis of GHG inventories and ecosystems carbon absorption in Brazil - da Costa, Luis Miguel [UNESP]; Davitt, Aaron; Volpato, Gabriela; de Mendonça, Gislaine Costa; Panosso, Alan Rodrigo [UNESP]; La Scala, Newton [UNESP] (Elsevier, 2025)
The global temperature is increasing mainly due to greenhouse gases (GHG) emissions in the last century. While the overall global increase in emissions is due to fossil fuel operations, Brazil has as its primary emitter from forestry and land use, and agriculture sectors. Though these sectors can emit, both can play an important role in mitigating global warming, due to the natural ecosystem and agroecosystem capability of carbon absorption. We aimed to understand the impact of carbon removal on Brazil's national inventory. For that, we compared two GHG inventories - Climate TRACE and SEEG - and explored how precipitation and photosynthesis impact their estimates to determine how the inventories capture seasonal variability. First, we compared the GHG emissions and removals estimates for each sector between both inventories, especially the Forestry and Land Use sector. Moreover, we performed correlation analysis and linear regressions between them, at a biome and pixel level between 2015 and 2022. Our results show that differences between the GHG inventories could reach 1 Giga ton of CO2 eq in some years, mainly due to the forestry sector. Furthermore, in some ecosystems, such as Caatinga, precipitation, and photosynthesis were increasing between 2015 and 2022, thus boosting the removal capacity in this biome. In 2022, the Caatinga GHG removal represented almost 50 % of the total removals in Brazil. A higher removal capacity could significantly contribute to achieving net-zero GHG emissions, especially if deforestation and other anthropogenic disturbances to ecosystems are halted. Our findings suggest that the Climate TRACE inventory captures more seasonal variability than SEEG. This outcome highlights the open issue of carbon removal estimates and also that seasonal aspects could be incorporated to improve our understanding.
Keywords: Carbon removals; Climate change; GHG inventory; Greenhouse gases